(3GdGJUGd GdOhdj h GdJcfhdhLjG GdMOjKI (B:s (3GdEfJQfJ(B- (3GdbeQ GdUhJj GdQbej(B- (3GdedJejOjG (B/s - (3Teh, Ydj eMeOs ((3GdShOGf (B:s (3OGQ GdbhejI GdYQHjI ddKbGaI h GdfTQ ,s, 2002)
(3jJfGhd GdcJGH JYQja GdGJUGd h fXeg hhSGFd GdGJUGd JYQja GdGJUGd GdOhdj h hhSGFdg GdHGH GdQGHY JcfhdhLjG GdGJUGd h GdhSGFd GdLOjOI GdHGH GdNGeS GdeJZjQGJ GdOhdjI aj eLGd GdGJUGds
(3HHdjhZQGajG (B: (3U(B.206s
Keywords: (3GdEfJQfjJs; (3GdJcfhdhLjG GdMOjKIs; (3GdedJejOjGs; (3GdEJUGd GdOhdjs